2017
DOI: 10.1111/bjd.15908
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of seborrhoeic dermatitis in a middle‐aged and elderly population: the Rotterdam Study

Abstract: SummaryBackground Seborrhoeic dermatitis is a chronic relapsing inflammatory skin disease with unclear pathophysiological mechanisms. Objectives To establish which lifestyle and physiological determinants are associated with seborrhoeic dermatitis. Methods Seborrhoeic dermatitis was diagnosed by a trained physician during a full-body skin examination within the Rotterdam Study, a prospective population-based cohort study in middle-aged and elderly people. The current design is a comparative cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 37 publications
4
60
2
6
Order By: Relevance
“…Additionally, there has been no evidence that Malassezia invades the skin, and pathogenic mycelial forms (hyphae) have not been observed in SD . Furthermore, M globosa tends to show increased growth in summer when temperatures are high and people sweat more, yet seasonal risk for SD is lowest in summer and higher in cold and dry winter . Besides, decrease in Malassezia count was not always detected in vivo even with improved SD symptoms upon ketoconazole treatment .…”
Section: Sd Aetiology: Malassezia Yeast—cause or Associated Factor?mentioning
confidence: 99%
“…Additionally, there has been no evidence that Malassezia invades the skin, and pathogenic mycelial forms (hyphae) have not been observed in SD . Furthermore, M globosa tends to show increased growth in summer when temperatures are high and people sweat more, yet seasonal risk for SD is lowest in summer and higher in cold and dry winter . Besides, decrease in Malassezia count was not always detected in vivo even with improved SD symptoms upon ketoconazole treatment .…”
Section: Sd Aetiology: Malassezia Yeast—cause or Associated Factor?mentioning
confidence: 99%
“…The authors concluded that this was due to increased xerosis and decreased barrier function in the winter, as well as possible UV protective effects during the summer. Dark‐skinned individuals might be less likely to seek care due to seborrheic dermatitis, possibly due to less striking erythema or improved barrier function compared with light‐skinned individuals …”
Section: What Is Seborrheic Dermatitis?mentioning
confidence: 99%
“…Only a few population‐based studies have been published on the prevalence of seborrhoeic dermatitis and on its occurrence in connection with other skin diseases. Some high‐quality prevalence studies focus on specific age groups such as the Rotterdam Study on an elderly population . Others focus on the systemic comorbidity of seborrhoeic dermatitis .…”
mentioning
confidence: 99%